Pemanfaatan Citra Landsat ETM+ dan Sistem Informasi Geografis untuk Pendugaan Limpasan Permukaan di DAS Jene’berang Hulu Provinsi Sulawesi Selatan - Nurfaika Nurfaika; Nurlina Nurlina (Jurnal Fisika FLUX, 2009)
River basin of Jene’berang is a main river in Gowa Regency of South Sulawesi. The aims of the research are: 1) to study ability of Landsat ETM+ imagery in collecting data and information of land physical parameter’s to estimate runoff coefficient, 2) to estimate and mapping spatial distribution of surface runoff using Landsat ETM+ and GIS application. The method in this research, were visual image interpretation for extraction landform and soilinfiltration parameter’s, and digital image interpretation for extraction landcover/landuse. Data image was Landsat ETM+ imagery. Evaluation result of interpretation Landsat ETM+ imagery used Short Method. The processing andanalyzing data used Geography Information System with overlay and scoring the based of Cook Method to yield spatial distribution of surface runoff map. The mapping unit used land unit approach the result of overlay map: landform, slopeand land use. Procedure of data collecting was used stratified proporsional  random sampling. The result of runoff coefficient was evaluated with hydrograph analyzing approach. The result of this research were: 1) the data of remote sensing could be used for estimation runoff coefficient. Interpretation of the landphysical parameter’s showed the accurate of the result Landsat ETM+ interpretation to the parameter landform 100%, the land cover/land use 88.37%, the soil infiltration 80%, and the slope started from surging to very steep difficultto interpretation of the Landsat ETM+ imagery, so it was needed secondary data such as digital contour map to extract DEM, 2) The upper of Jene’berang river basin had runoff coefficient distribution of normal class, high class, and extremeclass, the major class was the highest class. Runoff coefficient value 64.60 % its the highest class category.